An Aristotelian View of Marx's method - Nathaniel Cline; William McColloch; Kirsten Ford (The University of Utah, Department of Economics, 2011)
A number of Marxist scholars have tied aspects of Marx's thought to certain Aristotelian categories, yet remarkably little is said of Marx's dialectical materialism in this literature. Here we attempt to lay a foundation for such an effort, paying particular attention to the way in which Aristotle's mediated starting point resonates in Marx's method. While Hegel is able to grasp man's self-creation as a process, his dialectical method proceeds from an unmediated starting point, and impresses Idealism upon the Aristotelian categories. In rejecting the Idealist dimensions of Hegel's dialectic, Marx implicitly reclaims the materialist dimensions of Aristotle's system. It will be argued here that such an interpretation sheds important light on the nature of Marx's departure from Hegel, and on his method in Capital.
Keywords: B00; B14; B49; B51; 330; Marx; Aristotle; Hegel; Methodology